2008
DOI: 10.1007/978-3-540-88564-1_38
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Semantic Social Networks Using Virtual Reality

Abstract: Abstract. We present Redgraph, the first generic virtual reality visualization program for Semantic Web data. Redgraph is capable of handling large data-sets, as we demonstrate on social network data from the U.S. Patent Trade Office. We develop a Semantic Web vocabulary of virtual reality terms compatible with GraphXML to map graph visualization into the Semantic Web itself. Our approach to visualizing Semantic Web data takes advantage of user-interaction in an immersive environment to bypass a number of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A commonly explored representation is node-link diagrams. Halpin et al implemented a generic semantic social network visualization software for CAVE-like environments, named Redgraph, and, in a user study, observed significant performance improvements for fine-grained questions using the immersive condition [HZBK08]. Kwon et al explored different techniques in an HMD-based environment, proposing the use of a new spheric layout that offered performance increase especially for more difficult tasks [KMLM16].…”
Section: Related Workmentioning
confidence: 99%
“…A commonly explored representation is node-link diagrams. Halpin et al implemented a generic semantic social network visualization software for CAVE-like environments, named Redgraph, and, in a user study, observed significant performance improvements for fine-grained questions using the immersive condition [HZBK08]. Kwon et al explored different techniques in an HMD-based environment, proposing the use of a new spheric layout that offered performance increase especially for more difficult tasks [KMLM16].…”
Section: Related Workmentioning
confidence: 99%
“…Virtual reality offers the possibility of fully exploring complex datasets by using powerful interactive visualizations. For example, Redgraph 82 allows users to visualize semantic social networks in a virtual reality-based environment supported by the Computer-Assisted Virtual Environment 83 (CAVE). Users can interact with the visualization in order to contextualize graph nodes by clicking on them in order to fetch relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…Büschel et al [26] evaluated different edge styles for AR graphs and found that curved edges are harder to interpret. Halpin et al [7] initialized their VR scene with a 2D graph layout. Users could interactively "extrude" nodes to the third dimension to explore the social network.…”
Section: Related Workmentioning
confidence: 99%